Intraoperative fluid management in septic shock of abdominal origin guided by Fick´s formula vs ΔPCO2 - Romero, Vania; Flores, Rosa M.; Meneses, Hugo E. (International Journal of Research in Medical Sciences, 2024)
Background: In the main causes of morbidity and mortality in world is sepsis. Dynamic evaluations have more accurate predicting fluid response. Methods: It has made an observational, comparative, prospective, longitudinal and unicentric study. We included both sexes with 30-75 years and diagnosis of septic shock secondary to abdominal surgical pathology requiring surgical intervention. The sample was 36 patients. Two groups were be integrated; one group will be managed with Fick’s Formula and the other with ΔPCO2 with an equal number of participants in both groups, were aleatory, each group had 18 patients, three arterial and venous blood gas samples will be taken (pre-anesthetic, trans anesthetic and postanesthetic) to guide fluid management by means of cardiac output. Statistical analysis was made with, descriptive analysis for categorical variables with measures of central tendency and dispersion; inferential analysis for numerical variables with one-way Anova for comparison amount fluid administered guided by the formulas at the beginning, at a one hour and at the end of the surgical procedure subsequently Pearson’s correlation was applied. Results: When evaluating the amount of liquid administered in both groups by one-way ANOVA, no statistically significant difference was found, since the level of significance of both Fick’s formula and ΔPCO2 in their three measurements is higher to 0.05. We found for both high correlation with Pearson. Conclusions: There is no difference between the use of Fick´s formula or ΔPCO2. Regarding the liquids management, it is easier to apply ΔPCO2.